2018
DOI: 10.21107/rekayasa.v11i2.4446
|View full text |Cite
|
Sign up to set email alerts
|

Keragaman Populasi Pohon Asam (Tamarindus indica L.) di Jalan Raya Socah-Arosbaya, Kabupaten Bangkalan dan Strategi Konservasi

Abstract: <p><em>Pohon asam (Tamarindus indica) sangat sesuai untuk peneduh dan lanskaping karena bentuk tajuknya rindang, daunnya kecil-kecil, rantingnya kuat dan tidak mudah patah. Tujuan dari penelitian ini adalah untuk mengetahui populasi pohon asam di sepanjang Jl. Raya Socah-Arosbaya, Kabupaten Bangkalan. Survei dilaksanakan pada Juni-Agustus 2018 dengan metode purposive sampling mulai dari jalan raya Socah dengan koordinat 7°05'48.6"LS 112°42'44.3"BT sampai Jalan raya Gebang Arosbaya yang berada di ko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…Buah polong yang menggelembung, berbiji sampai 10 butir, kulit buah (eksokarp) mengeras berwarna kecokelatan bersisik. Daging buah (mesocarp) berwarna putih kehijauan saat masih muda, coklat kemerahan hingga hitam saat masak, asam manis dan lengket (Setiawan, 2018).…”
Section: A Pendahuluanunclassified
“…Buah polong yang menggelembung, berbiji sampai 10 butir, kulit buah (eksokarp) mengeras berwarna kecokelatan bersisik. Daging buah (mesocarp) berwarna putih kehijauan saat masih muda, coklat kemerahan hingga hitam saat masak, asam manis dan lengket (Setiawan, 2018).…”
Section: A Pendahuluanunclassified
“…Figure 6 could be used as preliminary information in the city mapping and FTS selection. This approach has traditionally achieved great success in Java, for example, tamarinds on Daendels Road [34].…”
Section: Reviving Cities With Fruit Tree Speciesmentioning
confidence: 99%
“…However, in Semarang City-Central Java, Roesmanto [33] noted that arenga palms (Arenga pinnata), coconuts, lontar trees, and asam kranji (Pithecellobium dulce), classified as FTS in the present study, were replaced by flowering ornamentals due to the changing preferences of city residents. In Bangkalan City, Madura Island, Setiawan [34] reported that the local government replaced tamarind trees along the roadside with fastgrowing angsana and glodokan tiang (Polyalthia longifolia) due to substantial damage by illegal cutting for making bonsai and tree death caused by the posting of election campaign signs. In other cases, trees along roadsides were destroyed following road improvements for handling a higher traffic load [137].…”
Section: Challenges For Sustainabilitymentioning
confidence: 99%